Examination of the Internal Control Systems in the Procedure of Receiving and Returning Collateral at Pegadaian Sharia - Nasution, Alya Elva Lianda; Juliati Nasution, Yenni Samri; Nurwani, Nurwani (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
The purpose of this study is to find out and evaluate the implementation of the internal control system for the receipt and return of Sharia Pawnshop collateral.This research is qualitative, using the case study method. The subject of this research is Pegadaian Syariah ar Hakim, Medan, Indonesia, and the object of the research is the implementation of an internal control system for the return of collateral. Data collection techniques use interviews, direct observation, and documentation.The results of the study found that the implementation of the internal control system for the return of collateral still needs to be improved, especially in management, Because there are still dual positions in the administrative department, this may cause fraud and ultimately weaken internal control, especially in the procedure for receiving and returning collateral.